(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The safe and effective option for the therapeutic management of psoriasis was attempted by preparing transferosomes of Betamethasone valerate (BV) and incorporating into formulation of gel to get more skin permeation, more effectiveness in drug entrapment and sustained release. Batches of experimental design of transferosome containing 100 mg of BV were produced by using Lipova E 80 and Span 20 as surfactant in varying quantities and incorporated in 1.5% HPMC gel base. Formulation was optimized to attain maximum drug entrapment, % drug release, ex-vivo permeation, pH, viscosity, spreadability and extrudability. The size and stability was ascertained by using Zeta sizer and and TEM was utilized to assess the surface morphology. The optimized formulation entrapped 59.87 % of the drug, pH 6.57, the average size of the particle was found to be 108.93 nm and viscosity were 436.19 centipoise.The residual analyses by gas chomatography confirms the elimination of formulation’s organic solvent and stability studies were conducted in accordance of the ICH guidelines. The developed formulation showed diffusion of BV through the rat’s skin at sustained rate for 10 hrs while marketed preparation sustained for 7 hrs only. It promises of localized action at the affected psoriatic sites for prolonged period with better release characteristics as compared to marketed formulation. The optimized formulation was found to be stable during the period of study.